2014
DOI: 10.1177/1357633x14552388
|View full text |Cite
|
Sign up to set email alerts
|

A review of the efficacy and effectiveness of using telehealth for paediatric speech and language assessment

Abstract: We reviewed the literature relating to the use of telehealth for paediatric speech and language assessment. Four databases, and relevant reference lists, were searched for articles published between January 2004 and July 2014. A total of 180 articles were identified, of which only five were relevant. All studies assessed efficacy using method comparison techniques; no studies assessed effectiveness. The method comparison studies investigated the validity and/or reliability of speech and language assessment via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 31 publications
2
51
0
2
Order By: Relevance
“…Interestingly, all of the reviewed studies utilised real-time videoconferencing facilities, allowing the clinician and client to visualise each other. This finding is consistent with results from previous reviews ( Mashima & Doarn, 2008 ; Reynolds et al, 2009 ; Taylor, Armfield, Dodrill, & Smith, 2014 ), indicating that real-time interactions support the delivery of services and strongly influence the clinical outcomes achieved through telehealth. Delivering speech and language intervention services through real-time videoconferencing facilities is an effective method of service delivery as this medium most closely resembles in-person interactions through the transmission of auditory and visual signals at a distance ( Mashima & Doarn, 2008 ; Reynolds et al, 2009 ).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, all of the reviewed studies utilised real-time videoconferencing facilities, allowing the clinician and client to visualise each other. This finding is consistent with results from previous reviews ( Mashima & Doarn, 2008 ; Reynolds et al, 2009 ; Taylor, Armfield, Dodrill, & Smith, 2014 ), indicating that real-time interactions support the delivery of services and strongly influence the clinical outcomes achieved through telehealth. Delivering speech and language intervention services through real-time videoconferencing facilities is an effective method of service delivery as this medium most closely resembles in-person interactions through the transmission of auditory and visual signals at a distance ( Mashima & Doarn, 2008 ; Reynolds et al, 2009 ).…”
Section: Discussionsupporting
confidence: 92%
“…Very good levels of inter-and intra-rater agreement were found on all measures with some variation between subtests (k range from 0.93 to >0.99). A limitation of this study, as noted by Taylor et al, 13 is that it was not conducted in real world settings but rather under ideal research conditions. In addition, none of the studies reported client or clinician satisfaction and only Ciccia et al reported on parent satisfaction.…”
Section: Telehealth In Speech-language Pathologymentioning
confidence: 95%
“…We believe this is sensible and would be typical in how face-to-face services transition to telepractice. However, emerging evidence also supported that telepractice is a viable and reliable means for screening or assessment in specific areas, including articulation screening, 26 aphasia assessment, 27 and poststroke dysphagia evaluation. 15 The use of telepractice in assessment and screening is likely to be more common as SLPs gather experience on this model of service delivery.…”
Section: Comparison Of Telepractice: Hong Kong and Other Parts Of Thementioning
confidence: 99%